Analiza efektywności klasyfikacji kredytobiorców uzyskanej zagregowanymi drzewami klasyfikacyjnymi dla prób o różnej strukturze - Chrzanowska, Mariola; Witkowska, Dorota (Efficiency Analysis of the Borrowers Classification Obtained by Aggregated Classification Trees for Different Structure of Sample, 2008)
In the paper we present the results of investigation that are conducted for the dichotomous classification of borrowers, employing actual data from the bank. For our research we construct several classification models applying ensemble classification. These models are built on the basis of 3 samples with different structure of credible and incredible clients. The first sample is symmetric (i.e. count of representatives of both groups is the same), the second one contains 9.4% incredible clients (as it was observed in Poland in the first two quarters of 2006), and the third sample contains 16% of noncreditworthy clients (as it was observed in the investigated bank). The aim of the investigation is to evaluate if different structure of the sample influences the quality of the classification.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 7, s. 232-239